Seeds that clean water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Engineers from the Department of Microbiology at the University of Leicester are testing a prototype water decontamination system using seeds from the tree Moringa oleifera. This tree popularly called the horseradish tree, is widespread in Africa,...